United States Policy in Africa - Wisner, Frank G. (Tufts Archival Research Center, 2005)
Volume 9, Issue 1. Winter Frank G. Wisner is currently Senior Deputy Assistant Secretary of State for African Affairs in the U.S. Department of State. In this capacity he recently has been engaged in the so-called "contact group" negotiations with the parties to the dispute in southern Africa. He is a career foreign service officer whose most recent prior postings have been Director and Deputy Executive Secretary of the Office of Southern African Affairs (1976-1979), and Ambassador to Zambia (1977-1982). In this interview, Ambassador Wisner outlines the major interests and policy objectives of the United States on the continent of Africa, focusing especially on the issues of southern Africa. He describes the U.S. policy of constructive engagement with respect to South Africa and its participation in negotiations aimed at reducing tensions in the region, expressing the view that only through such direct contacts can the U.S. hope to reduce the violence and oppression prevalent in the region and thereby create conditions which can expedite its social and economic development.